1999
DOI: 10.1111/1467-8659.00361
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Curve and Surface Representation: Reversing Subdivision Rules by Least‐Squares Data Fitting

Abstract: This work explores how three techniques for defining and representing curves and surfaces can be related efficiently. The techniques are subdivision, least‐squares data fitting, and wavelets. We show how least‐squares data fitting can be used to “reverse” a subdivision rule, how this reversal is related to wavelets, how this relationship can provide a multilevel representation, and how the decomposition/reconstruction process can be carried out in linear time and space through the use of a matrix factorization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 11 publications
(19 reference statements)
0
62
0
4
Order By: Relevance
“…In this operation, as clarified already, the coarse points f k and the matrix P are given, whereas the fine points f k+1 are the unknown yielded by them. The subdivision (forth) operation may be reversed [19], such that the fine points f k+1 and the matrix P are given, whereas the coarse points f k are the unknown yielded by them. That reverse (back) operation works by finding the solution to the least-squares system in Equation (2b)…”
Section: Perturbed Subdivision Schemesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this operation, as clarified already, the coarse points f k and the matrix P are given, whereas the fine points f k+1 are the unknown yielded by them. The subdivision (forth) operation may be reversed [19], such that the fine points f k+1 and the matrix P are given, whereas the coarse points f k are the unknown yielded by them. That reverse (back) operation works by finding the solution to the least-squares system in Equation (2b)…”
Section: Perturbed Subdivision Schemesmentioning
confidence: 99%
“…In [19], the traditional reverse subdivision problem is hence formulated by Equation (10a) and solved by Equation (12 In [8,9], the primal and the dual rules (or matrices) trees are shown to extend the standard MRA synthesis (inverse wavelet transform, Equation (11)) and analysis (wavelet transform, Equation (12)) cascades, respectively. The 'generalized perturbed schemes' synthesis model [9] and the 'subdivision regression' analysis model (here, Section 2) are associated with these MRA synthesis and analysis, respectively.…”
Section: Perturbed Subdivision Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…By generalizing the uniform subdivision in topology to a new irregular subdivision scheme, Valette and Prost [2,3] extended the work of Lounsbery and proposed a wavelet-based multiresolution analysis, to be applied directly to irregular meshes whose connectivity is unchanged in the wavelet analysis. Samavati et al [4] showed how to use least-squares data fitting to reverse subdivision rules and constructed the wavelets by straightforward matrix observations. Samavati et al [5] constructed multiresolution surfaces of arbitrary topologies by locally reversing the Doo-Sabin subdivision scheme.…”
Section: Related Workmentioning
confidence: 99%